The Corrective Feedback in the Students’ Speaking Ability: A Comparative Study - Napitupulu, Selviana; Napitupulu, Fenty Debora; Kisno, Kisno (Journal of Language Development and Linguistics, 2024)
This study investigated whether extensive and comprehensive oral recasting is more effective than explicit correction. The primary focus was on how feedback affects English language learning. Recasts that are intensive are defined as those that receive feedback on a single topic, whereas extensive feedback is defined as errors on multiple subjects and domains. Four groups of ten students each were formed from forty students from a Senior High School. A general English book called Think 4, a storybook, and an English grammar book called Grammar in Use were the study's instruments. In line with the study's aims, they were given feedback that was either explicit or implicit, thorough or in-depth. In accordance with the study's aims, they were given feedback that was either explicit or implicit, long or brief. The findings showed that there wasn't much of a difference between students who got implicit and explicit feedback. Additionally, it was discovered that every technique had the same effect on students' capacity to communicate.